The epigallocatechin gallate derivative Y6 inhibits human hepatocellular carcinoma by inhibiting angiogenesis in MAPK/ERK1/2 and PI3K/AKT/ HIF-1α/VEGF dependent pathways. (15th September 2020) - Liao, Zhi-Hong; Zhu, Hong-Qing; Chen, Yan-Yan; Chen, Run-Li; Fu, Li-Xiang; Li, Li; Zhou, Huan; Zhou, Jin-Ling; Liang, Gang
Abstract: Ethnopharmacological relevance: Hypervascularity has been considered as one of the major features of many solid tumors. Green tea is one of the commonly drink resources in China, and its active component, Epigallocatechin gallate (EGCG), exhibits antiangiogenic activities in various experimental tumor models. However, EGCG has many shortages, e.g., relatively unstable, low lipid solubility, poor bioavailability, and short duration of action. Aim of the study: To overcome the shortages of EGCG for antiangiogenic antitumor usage, our study developed a novel EGCG derivate, Y6 (5, 3′, 4′, 3″, 4″, 5″-6-0-ethyl-EGCG). The underlying mechanism was also elucidated. Material and methods: we evaluated the effects of EGCG, Y6 on HCC and angiogenesis in vivo and in vitro. Moreover, to understand their antitumor mechanisms, key factors within angiogenesis-related signaling pathways (MAPK/ERK1/2, PI3K/AKT, HIF-1 VEGF) were analyzed by using western blot, immunohistochemistry (IHC), quantitative real-time quantitative PCR (RT-PCR). HepG2 xenograft model and the chorioallantoic membrane (CAM) were used to investigate the effects of Y6 and EGCG on tumors and anti-angiogenesis in vivo. Micro-vessel density (MVD) was analyzed by IHC of CD34 staining. IHC, qRT-PCR and Western blot were used to detect the expression of HIF-1α and VEGF protein in tumor tissues. The protein levels of MAPK/ERK1/2, PI3K/AKT, HIF-1α, and VEGF in tumor tissues were detected by western blot. Results: Our results demonstrated that both EGCG and Y6 displayed antiangiogenetic and antitumor effects against HCC cells in vitro and in vivo . We found that rather than equal amount of EGCG, Y6 displayed better abilities in inhibiting the growth of HCC tumor cells, as well as inhibiting the growth of neovascularization in the chick embryos and HepG2 xenograft tumors bearing-mice, based on the data obtained from MTT assay, immunohistochemistry (IHC), chick chorioallantoic membrane (CAM) assays. In the comparison of equivalent dose of EGCG, qRT-PCR data showed that Y6 induced more significant decrease of the mRNA levels of HIF-1α and VEGF in supernatant-treated SMMC-7721 cells under hypoxic condition, as well as in the in xenograft tumor tissues; whereas Y6 also significantly reduced the protein levels of MAPK/ERK1/2, PI3K/AKT, HIF-1α, and VEGF to a greater extent than EGCG, determined by western blotting assay. Conclusions: our work suggests that the new EGCG derivate Y6 could significantly inhibit tumor growth and angiogenesis which is possibly involved with the signaling intervention of MAPK/ERK1/2 and PI3K/AKT/HIF-1α/VEGF pathways, and is supposed to be a potential therapeutic reagent for anti-angiogenesis treatment of solid tumors. Graphical abstract: Different concentrations of Y6 and EGCG group compared with the control group, the inhibition of chorioallantoic membrane (CAM) angiogenesis was significant. It indicated that it is a potential new vascular inhibitor, which may be a new treatment option for anti-angiogenic therapy in solid tumors. Image 1